The Effect of Oil Prices on Industrial Production in Oil-importing Countries: Panel Cointegration Test - Kalymbetova, Aigul; Zhetibayev, Zhanture; Kambar, Raushan; Ranov, Zhandos; Izatullayeva, Bibigul (International Journal of Energy Economics and Policy, 2020)
The industrialization levels of the countries are an indicator of development. Countries trying to increase their production in the industrial sector prefer to have access to energy in a cheap and easy way. However, economies that do not have sufficient energy reserves may be affected by the changes in energy prices since they will import the necessary energy input. Although there are many studies discussing the effects of energy or oil prices on macroeconomic variables in countries, the research based on industrial production is limited. In this study, the long-term relationship between the changes in oil prices and industrial production in the ten most oil-importing countries (China, Germany, India, Italy, Japan, Netherlands, South Korea, Spain, United Kingdom and United States) was analyzed by Pedroni, Kao and Johansen Fisher cointegration tests. According to the empirical findings of the study, it is concluded that the relationship between the industrial production of oil importing countries and oil prices is positive. This situation can be interpreted as these countries with high levels of industrialization process the crude oil and market the products they produce to foreign countries more profitably. Keywords: oil price, import, industrial production index, panel cointegration, FMOLS, DOLS JEL Classifications: O10, Q30, Q43 DOI: https://doi.org/10.32479/ijeep.10439